Different responses to DNA damage determine ageing differences between organs. Issue 4 (4th March 2022) - Vougioukalaki, Maria; Demmers, Joris; Vermeij, Wilbert P.; Baar, Marjolein; Bruens, Serena; Magaraki, Aristea; Kuijk, Ewart; Jager, Myrthe; Merzouk, Sarra; Brandt, Renata M.C.; Kouwenberg, Janneke; van Boxtel, Ruben; et al.
Abstract: Organs age differently, causing wide heterogeneity in multimorbidity, but underlying mechanisms are largely elusive. To investigate the basis of organ‐specific ageing, we utilized progeroid repair‐deficient Ercc1 Δ /− mouse mutants and systematically compared at the tissue, stem cell and organoid level two organs representing ageing extremes. Ercc1 Δ /− intestine shows hardly any accelerated ageing. Nevertheless, we found apoptosis and reduced numbers of intestinal stem cells (ISCs), but cell loss appears compensated by over‐proliferation. ISCs retain their organoid‐forming capacity, but organoids perform poorly in culture, compared with WT. Conversely, liver ages dramatically, even causing early death in Ercc1 ‐KO mice. Apoptosis, p21, polyploidization and proliferation of various (stem) cells were prominently elevated in Ercc1 Δ /− liver and stem cell populations were either largely unaffected (Sox9+), or expanding (Lgr5+), but were functionally exhausted in organoid formation and development in vitro . Paradoxically, while intestine displays less ageing, repair in WT ISCs appears inferior to liver as shown by enhanced sensitivity to various DNA‐damaging agents, and lower lesion removal. Our findings reveal organ‐specific anti‐ageing strategies. Intestine, with short lifespan limiting time for damage accumulation and repair, favours apoptosis of damaged cells relying on ISC plasticity. Liver with low renewal rates depends more on repair pathways specifically protecting the transcribed compartment of the genome to promote sustained functionality and cell preservation. As shown before, the hematopoietic system with intermediate self‐renewal mainly invokes replication‐linked mechanisms, apoptosis and senescence. Hence, organs employ different genome maintenance strategies, explaining heterogeneity in organ ageing and the segmental nature of DNA‐repair‐deficient progerias. Abstract : Organs age differently. To investigate the basis of organ‐specific ageing we systematically compared at the tissue, stem cell and organoid level two organs representing ageing extremes, from accelerated aged, repair‐deficient Ercc1 Δ /− mouse mutants. Very short‐lived cells, such as those of intestinal epithelium, have low damage tolerance and opt primarily for apoptosis and cell replacement. On the other extreme, liver (and by inference also neuronal tissue) with long‐lived cells, invest in cell survival by damage sensing and repair primarily linked with the transcribed compartment. They also may have high damage tolerance and consequently higher senescence levels. The differences in genome maintenance strategies we reveal, explain heterogeneity in organ ageing and the segmental nature of DNA‐repair‐deficient progerias.